Cost-Effectiveness of Maternal Tetanus Toxoid and Tetanus Diphtheria in Developing Countries: Systematic Review - Ana Claudia da Costa Guterres; Sri Annisapada Jamaru; Tiara Mudrika; Azizah Yuhani; Sulistyaningsih; Putri Listiani (Journal Of Nursing Practice, 2026)
Background: Maternal and neonatal tetanus (MNT) remains a public health threat in low- and middle-income countries due to suboptimal coverage of complete-dose maternal immunization. Although TT and Td vaccines are clinically effective, their cost-effectiveness in different country contexts needs systematic assessment. Purpose: To evaluate the cost-effectiveness of maternal tetanus toxoid (TT) and tetanus-diphtheria (Td) vaccination in developing countries, focusing on economic outcomes and contextual variations. Methods: This systematic review followed PRISMA 2020 guidelines. Literature was searched in PubMed, Scopus, ScienceDirect, Wiley, and Crossref. Inclusion criteria comprised CEA/CUA studies on maternal TT/Td immunization in developing countries. Reporting quality was assessed using the CHEERS 2022 checklist. Results: From 2,040 records, four studies met inclusion criteria. All reported maternal TT/Td vaccination as highly cost-effective, with ICERs ranging from USD 3.61 to 15,600 per DALY or life-year saved. Key uncertainties included vaccine effectiveness and distribution costs, while program efficiency varied by local health system conditions. Conclusion: Complete-dose maternal TT/Td immunization is a highly cost-effective public health intervention in resource-limited settings. However, policy implementation must be adapted to local contexts and supported by robust sensitivity analysis and reliable primary data.